Soluble forms of the adhesion molecule E-cadherin in urine. Issue 2 (February 1995) - Banks, R E; Porter, W H; Whelan, P; Smith, P H; Selby, P J
Abstract : The adhesion molecule E-cadherin is essential for maintaining epithelial intercellular adhesion. Loss or reduced expression of E-cadherin has been related to invasive behaviour in a wide range of carcinomas. Using immunoblotting techniques, the existence of multiple soluble forms of E-cadherin was demonstrated in urine from healthy volunteers and patients with benign urinary tract disorders or bladder cancer. The existence of soluble forms of E-cadherin in the urine may reflect shedding from the urinary tract epithelium as part of the normal turnover of this molecule. The possibility that enhanced shedding may contribute to the loss of E-cadherin expression/function in malignancy is discussed.